Simulations of decane-ammonia autoignition in two mixture fractions - Kylikas, Angelos; Mastorakos, Epaminondas (Frontiers in Mechanical Engineering, 2025)
This paper presents a zero-dimensional Doubly Conditional Moment Closure (0D-DCMC) methodology for investigating dual-fuel combustion involving ammonia and diesel. The approach uses two mixture fractions as conditioning variables, one for each fuel, to effectively model ignition and reveal the flame structure in mixture fraction space. Initially, 0D reactor calculations are performed using Cantera, exploring the chemical mechanism, identifying the most reactive mixture fractions, and determining key species involved in the ignition process. Following that, the 0D-DCMC simulations carried out provide understanding into the effects of the scalar and cross-scalar dissipation rates on autoignition. The results show that higher scalar dissipation rates delay ignition, while a negative cross-scalar dissipation rate reduces ignition delay compared to a positive rate. The ignition is shown to occur near the most reactive mixture fraction of the most reactive fuel, at lower conditional values of the less reactive fuel’s mixture fraction. The species fronts formed are observed to follow a trajectory between the stoichiometric mixture fractions of the fuels. The results establish a robust computational framework for modeling dual-fuel combustion.